2014
DOI: 10.7322/jhgd.79915
|View full text |Cite
|
Sign up to set email alerts
|

A policy pathway to reducing teenage pregnancy in Africa

Abstract: Background: Teenage pregnancy remains an important and complex issue around the world, with reports indicating that Africa has higher rates than other continents. Studies have indicated that social and economic determinants are associated with these higher rates. Therefore this study aims to identify the social and economic influencers of teenage pregnancy which would help develop a best-practice approach to reduce its incidence in Africa. Methods: Data sets from the World Bank Organisation between 2008 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
1
10
2
3
Order By: Relevance
“…While observed patterns at community level (i.e an inverse association between teenage childbearing and community wealth or female education) are consistent with previous research (Gupta and Mahy, 2003), there is no evidence of similar associations with national wealth or female education. Although a recent analysis of World Bank data for 51 African countries identified both female literacy and GDP per-capita to have significant inverse bivariate correlations with teenage pregnancy (Odejimi and Bellingham-Young, 2014), this study provides no evidence that national female education is significant while GDP per capita shows an opposite pattern.…”
Section: Contextual Socio-economic Determinantscontrasting
confidence: 85%
See 2 more Smart Citations
“…While observed patterns at community level (i.e an inverse association between teenage childbearing and community wealth or female education) are consistent with previous research (Gupta and Mahy, 2003), there is no evidence of similar associations with national wealth or female education. Although a recent analysis of World Bank data for 51 African countries identified both female literacy and GDP per-capita to have significant inverse bivariate correlations with teenage pregnancy (Odejimi and Bellingham-Young, 2014), this study provides no evidence that national female education is significant while GDP per capita shows an opposite pattern.…”
Section: Contextual Socio-economic Determinantscontrasting
confidence: 85%
“…Limited evidence available from the developing countries include a recent analysis of World Bank data between 2008 and 2010 for 51 African countries which identified female literacy as the best predictor, while healthcare expenditure and GDP per capita also had a significant inverse relationship (based on bivariate correlations) with teenage pregnancy (Odejimi and Bellingham-Young, 2014). Other studies in SSA, not specific to adolescents, have identified community's socio-cultural environment and wealth status as important predictors of women's sexual behaviour, contraceptive and other reproductive health outcomes (Stephenson et al, 2007;Uthman and Kongnyuy, 2008).…”
Section: Socio-economic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Odejimi (2014), showed that literacy rates, contraceptive prevalence rates and health care spending rates were factors affecting teenage pregnancy. The results of logistic regression analysis in the study showed that literacy rate became the best predictor of teenage pregnancy in Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Este estudio explora estudios que han identificado factores que se cree que influyen en el embarazo adolescente en países desarrollados y en desarrollo. Se ha encontrado que el nivel de riqueza nacional, el ritmo de desarrollo económico y la magnitud de la desigualdad de ingresos dentro de los países están asociados con diferencias en las tasas de natalidad entre adolescentes (Klüsse, 2020) Un estudio realizado utilizando datos de 51 países africanos sobre estrategias y políticas que pueden implementarse para reducir el embarazo adolescente sugirió que mejorar la tasa de alfabetización femenina, el gasto en atención médica y el producto interno bruto (PIB) per cápita del país serán enfoques prácticos para abordar el embarazo adolescente (Odejimi, 2014). En Sudáfrica, hay una serie de programas de prevención orientados a reducir el embarazo adolescente.…”
Section: Desarrollounclassified